Analisis faktor-faktor yang berhubungan dengan pemanfaatan pelayanan kesehatan jiwa di wilayah kerja Puskesmas Seputih Raman Lampung Tengah - Yuniar Herdarini Utami; Khoidar Amirus; Dhiny Easter Yanti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Mental health service facilities are still not optimally utilized, especially at Seputih Raman Public Health Center.Purpose: To determine the factors associated with the utilization of family members' treatment for mental disorders at the Seputih Raman Public Health Center, Central Lampung.Method: A quantitative with a cross-sectional design. The research population is householders who have members with mental disorders in Seputih Raman Public Health Center area many as 123 people. The data analysis technique used univariate, bivariate (chi-square), and multivariate (multiple logistic regression) analysis.Results: Treatment utilization was relatively good (64.2%), good knowledge (53.7%), positive attitude (52%), good accessibility (50.4%), felt there was support from health workers (56.9%) and felt there was family support (65.9%) . The results of the hypothesis test showed that there was a relationship between knowledge (p=0.007; OR=3.0), attitude (p=0.002; OR=3.6), accessibility (p=0.004; OR=3.3), support from health workers (p=0.001; OR=3.7 ), family support (p=0.001; OR=2.2) with the use of treatment for family members with mental disorders. The most dominant factor is attitude (p=0.002; OR=4.0).Conclusion: There is a relationship between knowledge, attitudes, accessibility, support from health workers, family support, and the use of treatment for family members with mental disorders. And the most dominant factor is attitude.Suggestion: This study suggests that education and information accessibility should be carried out with household targets to increase the utilization of mental disorder treatment.Keywords: Utilization; Treatment; Family members; Mental disorders.Pendahuluan: Fasilitas layanan kesehatan jiwa masih belum optimal dimanfaatkan oleh orang dengan gangguan jiwa khususnya di Puskesmas Seputih Raman.Tujuan: Untuk diketahui faktor yang berhubungan dengan pemanfaatan pengobatan anggota keluarga dengan gangguan jiwa.Metode: Penelitian kuantitatif dengan desain cross sectional. Populasi penelitian KK yang memiliki anggota keluarga gangguan jiwa di Wilayah Puskesmas Seputih Raman yang berjumlah sebanyak 123 orang yang seluruhnya dijadikan sebagai sampel. Tehnik analisis data menggunakan analisis univariat, bivariat (chi square) dan multivariat (regresi logistik berganda).Hasil: Pemanfaatan pengobatan relatif baik (64.2%), pengetahuan baik (53.7%), sikap positif (52%), aksesibilitas baik (50.4%), merasa ada dukungan petugas kesehatan (56.9%) dan merasa ada dukungan keluarga (65.9%). Hasil uji hipotesis menunjukkan ada hubungan pengetahuan (p=0.007;OR=3.0), sikap (p=0.002;OR=3.6), aksesibilitas (p=0.004;OR=3.3), dukungan petugas kesehatan (p=0.001;OR=3.7), dukungan keluarga (p=0.001;OR=2.2) dengan pemanfaatan pengobatan anggota keluarga dengan gangguan jiwa. Faktor yang paling dominan adalah sikap (p=0.002;OR=4.0).Simpulan: Ada Hubungan antara pengetahuan, sikap, aksesibilitas, dukungan petugas kesehatan, dukungan keluarga dengan pemanfaatan pengobatan anggota keluarga dengan gangguan jiwa. Dan faktor paling dominan adalah sikap.Saran: Penelitian ini menyarankan agar dilakukan edukasi dan aksesibilitas informasi dengan sasaran rumah tangga untuk meningkatkan pemanfaatan pengobatan gangguan jiwa.